(untitled) (Palimpsesto, 2025)
This study examines the representation of sexual diversity, focusing on bisexuality and multiple orientations, in four contemporary Chilean literary works: Coyhaiqueer (Coñuecar, 2018), No te ama (Gutiérrez, 2015), Aprende a Amar[te] (Torres Castillo, 2019), and A ti siempre… (García Mendoza, 2016). Drawing on Hemmings and Yoshino’s bisexual framework, it explores aesthetic-discursive strategies and identity-desire tensions. Results reveal strategies of bisexual erasure, yet emerging aesthetics challenging mononormative binaries are noted. The study underscores the need to expand representations and research on bisexuality in Chilean literature.